2017
DOI: 10.22159/ajpcr.2017.v10i2.14762
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Drug Utilization Pattern of the Geriatric Patients in the Department of Geriatric Medicine in a Tertiary Care Hospital in Assam, India

Abstract: Objective: To investigate the drug utilization pattern and the prevalence of potentially inappropriate medications (PIMs) using updated AGS Beers Criteria 2012 among the elderly patients who attended the geriatric outpatient departments as well as admitted indoor patients in a Tertiary Care Hospital at Guwahati, Assam, India. Methods:A hospital-based prospective, observational and cross sectional study, involving patients aged 65 years and above was planned and conducted over a period of 6-months from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Sample size varied on regional basis from 90 to 1,510, making a total of 11,649 patients. All the studies included both women and men ( Bhatt et al, 2019 ; Chandrasekhar et al, 2019 ; Motallebzadeh et al, 2019 ; Pradhan and Panda, 2018 ; Benjamin et al, 2018 ; Devarapalli et al, 2017 ; Kumar et al, 2017 ; Pradhan et al, 2017 ; Narvekar et al, 2017 ; Borah et al, 2017 ; Rakesh et al, 2017 ; Anjum et al, 2017 ; Swathi and Bhavika, 2016 ; Salwe et al, 2016 ; Chowta et al, 2016 ; Kashyap et al, 2015 ; Danisha et al, 2015 ; Umar et al, 2015 ; Undela et al, 2014 ; Dhikav et al, 2014 ; Karandikar et al, 2013 ; Momin et al, 2013 ; Nagendra et al, 2012 ; Shah et al, 2011 ; Mandavi et al, 2011 ; Zaveri et al, 2010 ; Harugeri et al, 2010 ); however, seven studies included more women than men( Dhikav et al, 2014 ; Umar et al, 2015 ; Salwe et al, 2016 ; Kumar et al, 2017 ; Narvekar et al, 2017 ; Bhatt et al, 2019 ; Chandrasekhar et al, 2019 ). Among the studies, nineteen were cohort design ( Chandrasekhar et al, 2019 ; Motallebzadeh et al, 2019 ; Pradhan and Panda, 2018 ; Benjamin et al, 2018 ; Devarapalli et al, 2017 ; Pradhan et al, 2017 ; Narvekar et al, 2017 ; Anjum et al, 2017 ; Salwe et al, 2016 ; Chowta et al, 2016 ; Kashyap et al, 2015 ; Danisha et al, 2015 ; Umar et al, 2015 ; Undela et al, 2014 ; Dhikav et al, 2014 ; Karandikar et al, 2013 ; Nagendra et al, 2012 ; Shah et al, 2011 ; Haruger...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size varied on regional basis from 90 to 1,510, making a total of 11,649 patients. All the studies included both women and men ( Bhatt et al, 2019 ; Chandrasekhar et al, 2019 ; Motallebzadeh et al, 2019 ; Pradhan and Panda, 2018 ; Benjamin et al, 2018 ; Devarapalli et al, 2017 ; Kumar et al, 2017 ; Pradhan et al, 2017 ; Narvekar et al, 2017 ; Borah et al, 2017 ; Rakesh et al, 2017 ; Anjum et al, 2017 ; Swathi and Bhavika, 2016 ; Salwe et al, 2016 ; Chowta et al, 2016 ; Kashyap et al, 2015 ; Danisha et al, 2015 ; Umar et al, 2015 ; Undela et al, 2014 ; Dhikav et al, 2014 ; Karandikar et al, 2013 ; Momin et al, 2013 ; Nagendra et al, 2012 ; Shah et al, 2011 ; Mandavi et al, 2011 ; Zaveri et al, 2010 ; Harugeri et al, 2010 ); however, seven studies included more women than men( Dhikav et al, 2014 ; Umar et al, 2015 ; Salwe et al, 2016 ; Kumar et al, 2017 ; Narvekar et al, 2017 ; Bhatt et al, 2019 ; Chandrasekhar et al, 2019 ). Among the studies, nineteen were cohort design ( Chandrasekhar et al, 2019 ; Motallebzadeh et al, 2019 ; Pradhan and Panda, 2018 ; Benjamin et al, 2018 ; Devarapalli et al, 2017 ; Pradhan et al, 2017 ; Narvekar et al, 2017 ; Anjum et al, 2017 ; Salwe et al, 2016 ; Chowta et al, 2016 ; Kashyap et al, 2015 ; Danisha et al, 2015 ; Umar et al, 2015 ; Undela et al, 2014 ; Dhikav et al, 2014 ; Karandikar et al, 2013 ; Nagendra et al, 2012 ; Shah et al, 2011 ; Haruger...…”
Section: Resultsmentioning
confidence: 99%
“…After removing 165 duplicates, a total of 1835 titles and abstracts were screened to determine if they met the inclusion criteria, as described in the methodology section. Full-text assessment of 119 potentially relevant articles resulted in 27 eligible studies (Bhatt et al, 2019;Chandrasekhar et al, 2019;Motallebzadeh et al, 2019;Pradhan and Panda, 2018;Benjamin et al, 2018;Devarapalli et al, 2017;Kumar et al, 2017;Pradhan et al, 2017;Narvekar et al, 2017;Borah et al, 2017;Rakesh et al, 2017;Anjum et al, 2017;Swathi and Bhavika, 2016;Salwe et al, 2016;Chowta et al, 2016;Kashyap et al, 2015;Danisha et al, 2015;Umar et al, 2015;Undela et al, 2014;Dhikav et al, 2014;Karandikar et al, 2013;Momin et al, 2013;Nagendra et al, 2012;Shah et al, 2011;Mandavi et al, 2011;Zaveri et al, 2010;Harugeri et al, 2010), as shown in Figure 1. The list of articles that are excluded (n 92) due to various reasons is presented in Supplementary Table S2.…”
Section: Study Selectionmentioning
confidence: 99%
“…Such use of high antibiotics may result in resistance. The percentage of injectable preparations used was 100% which is more than the studies performed by Borah et al (65%)[14] and Sharma et al(14.96%)…”
mentioning
confidence: 64%
“…The male predominance of polypharmacy among geriatrics is probably because they are more prone for multiple co-morbidities (Borah et al, 2017). The mean age of the study subjects was found to be 72.9 ± 6.5 years with a maximum of 95 years.…”
Section: Discussionmentioning
confidence: 88%